Prognostička vrednost HALP indeksa, sedimentacije eritrocita i reumatoidnog faktora u reumatoidnom artritisu: laboratorijska multivarijantna analiza: Prediction model of RA - Xu, Xiaohua; Huang, Xiaohua; Lu, Yongfang; Zeng, Defei (Journal of Medical Biochemistry, 2025)
Background: Biochemical and hematological indices play a critical role in evaluating systemic inflammation and disease activity in rheumatoid arthritis (RA). This study investigated the prognostic value of the hemoglobin–albumin–lymphocyte–platelet (HALP) index, in combination with erythrocyte sedimentation rate (ESR) and rheumatoid factor (RF), for predicting RA disease progression. Methods: A retrospective analysis was performed on 146 RA patients admitted between December 2022 and December 2023. Laboratory variables included HALP index, ESR, RF, C-reactive protein, anti-CCP antibodies, hemoglobin, albumin, lymphocyte and platelet counts, and serum creatinine. Measurements were obtained using standardized automated hematology and biochemical analyzers. Disease activity and radiographic joint damage scores were also assessed. Statistical approaches included correlation analysis, regression analysis, and receiver operating characteristic (ROC) curve evaluation. Results: The HALP index, ESR, and RF were significantly associated with RA disease progression. The HALP index demonstrated a strong correlation with disease activity (r=0.602, P<0.001). ROC analysis showed an area under the curve (AUC) of 0.858 for HALP, 0.841 for ESR, and 0.924 for RF. When combined in a multivariate regression model, the predictive performance improved (AUC=0.943). Conclusion: The HALP index, as a composite biochemical marker, in combination with ESR and RF, provides significant prognostic information for RA progression. These findings underscore the importance of laboratory-based indices in refining prognostic assessments and highlight their potential role in personalized disease management.